2016
DOI: 10.1177/1070496516672263
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Weak Links of Solid Waste Management in Informal Settlements

Abstract: Many cities in the global South suffer from vast inadequacies and deficiencies in their solid waste management. In the city of Kisumu in Kenya, waste management is fragmented and insufficient with most household waste remaining uncollected. Solid waste enters and leaves public space through an intricate web of connected, mostly informal, actions. This article scrutinizes waste management of informal settlements, based on the case of Kisumu, to identify weak links in waste management chains and find neighborhoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 49 publications
3
49
0
2
Order By: Relevance
“…Although there is a lack of reliable data, our field studies (Gutberlet et. al., 2016) demonstrated how SWM in Kisumu continues to suffer from weak finances, feeble political and institutional support, poor community attitudes and lack of a systematic approach as was observed already in 2008 (Onyango and Kibwage, ).…”
Section: Results: the Reconstruction Of Waste Management In Kisumu's mentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a lack of reliable data, our field studies (Gutberlet et. al., 2016) demonstrated how SWM in Kisumu continues to suffer from weak finances, feeble political and institutional support, poor community attitudes and lack of a systematic approach as was observed already in 2008 (Onyango and Kibwage, ).…”
Section: Results: the Reconstruction Of Waste Management In Kisumu's mentioning
confidence: 99%
“…The result is a massive accumulation of waste on foot paths and empty lots, in drains, along roadsides and at the locations where the waste skips used to be located when still operated through KISWAMP. However, services of small private entrepreneurs are gaining ground also in the informal settlements among those households that can afford a small fee for collection (Gutberlet et. al., 2016).…”
Section: Results: the Reconstruction Of Waste Management In Kisumu's mentioning
confidence: 99%
“…Today, Kisumu is home to a population of about 500 000 and had an estimated growth rate of 2.8% per year in 2006 (Geissler 2013;UN-Habitat 2006). It is the third largest city in Kenya (after Nairobi and Mombasa), and is one of Kenya's fastest growing cities (Gutberlet et al 2017). Population figures are somewhat speculative, particularly since the redrawing of Kisumu's census areas.…”
Section: Kisumu City Kenyamentioning
confidence: 99%
“…Observations indicated that solid waste management is a pressing issue and a significant environmental and public health challenge in all the case study cities. In Kisumu and Kitwe, only 20-25% of the waste generated is adequately collected and properly disposed of at landfills (Gutberlet et al 2017;Magezi 2015). These waste collection services are provided by both the government and the private sector and mostly concentrated in middle-and highincome areas (Gutberlet et al 2017;Magezi 2015).…”
Section: Inadequate Waste Disposal and Poor Resource Efficiencymentioning
confidence: 99%
See 1 more Smart Citation